Intercultural Interaction - Spencer-Oatey, H. author. aut Link
XV, 367 p. 149 illus.
Keywords: Written in a highly accessible style and in four parts, this book provides rapid and authoritative access to current ideas and practice in intercultural communication. It draws on concepts and findings from a range of different disciplines and uses authentic examples of intercultural interaction to illustrate points.